Hybrid diphosphorus ligands in rhodium catalysed asymmetric hydroformylation - Chikkali, Samir H.; van der Vlugt, Jarl Ivar; Reek, Joost N. H. (Coordination Chemistry Reviews, 2014)
This review aims to illustrate recent advances in the application of hybrid diphosphorus ligands for the Rh catalysed hydroformylation of alkenes, discussing the most prevalent classes of hybrid systems, i.e. phosphine-phosphinite, phosphine-phosphonite, phosphine-phosphite, phosphite-phosphoramidite and phosphite-phosphoramidite and comparing their performance with relevant C-2 symmetric counterparts. In order to introduce the field and put the results in context, a short overview on Rh hydroformylation is provided. Available spectroscopic (in situ) data on the coordination modes of hybrid phosphorus ligands and the catalytic performance of these systems in asymmetric hydroformylation of vinyl arenes are reported. Potential avenues for future research are shortly discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Asymmetric hydroformylation; Catalyst resting state; Hybrid ligand design; In situ spectroscopy; Rhodium

Highly regioselective isomerizing hydroformylation of long-chain internal olefins catalyzed by a rhodium bis(phosphite) complex - Pandey, Swechchha; Chikkali, Samir H. (ChemCatChem, 2015)
The single-step synthesis, coordination behavior, and application of a bis(phosphite) ligand in the isomerizing hydroformylation of internal olefins was investigated. Interestingly, high-pressure NMR spectroscopy investigations revealed unexpected inequivalency of the two phosphorus nuclei, which display bisequatorial coordination of the bis(phosphite) ligand in a trigonal bipyramidal rhodium complex. Upon employment in the isomerizing hydroformylation of the exceedingly challenging plant oil derived substrate methyl oleate, the bis(phosphite) rhodium complex revealed an unprecedented linear selectivity of 75%.
Keywords: alkenes; bis(phosphite)s; Hydroformylation; isomerization; Rhodium

Highly enantioselective synthesis of sitagliptin - Khopade, V. Kishor; Sen, Anirban; Birajdar, Rajkumar S.; Paulbudhe, Uday P.; Kavale, Dattatry S.; Shinde, Prashant S.; Mhaske, Santosh B.; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2020)
A highly enantioselective synthesis of sitagliptin, a potent DPP-4 inhibitor, is reported. Explicitly identified chiral FerroLANE ligands in the presence of rhodium catalyze the asymmetric hydrogenation of an enamine to yield sitagliptin with excellent enantioselectivity (98% ee). The process was scaled up to 5 g and the final product was isolated as a phosphate salt with >99% ee.
Keywords: asymmetric hydrogenation; catalysis; FerroLANE ligands; Rhodium; sitagliptin